Formulation and Characterization of Carbamazepine Chitosan Nanoparticle - Citra Ariani Edityaningrum; Ariza Nur Zulaechah; Widyasari Putranti; Dewa Ayu Arimurni (Universitas Airlangga, 2022)
Background: Carbamazepine is an antiepileptic drug used to treat trigeminal neuralgia and pain associated with neurological disorders. The drug belongs to class II of the Biopharmaceutical Classification System (BCS), which has low solubility. Hence, dissolution is a rate-limiting step. Objective: This study aimed to determine the best formula for carbamazepine nanoparticles based on physical characteristics and determine the effect of chitosan and Na-TPP concentration variation on nanoparticle characterization. Methods: The carbamazepine chitosan nanoparticles were prepared using ionic gelation method with a concentration of 0.1% w/v carbamazepine and the ratio of chitosan and Na-TPP concentrations of 0.2%:0.1% (F1), 0.2%:0.2% (F2), and 0.3%:0.1% w/v (F3). The parameters evaluated included particle size, polydispersity index, zeta potential, particle morphology, and entrapment efficiency. Statistical analysis was conducted on the evaluation data using One Way ANOVA. Results: The results showed that the effect of increasing the concentration of chitosan reduced particle size (p<0.05), increased zeta potential (p<0.05), and had no effect on the value of entrapment efficiency (p>0.05). Furthermore, F3 had a particle size of 169.8±13.71 nm with a polydispersity index of 0.378±0.02, the zeta potential of +28.80±2.44 mV, entrapment efficiency of 84.3±7.50%, and spheric particle morphology which was measured using Transmission Electron Microscope (TEM). Conclusion: Therefore, F3 with the ratio of chitosan and Na-TPP concentrations of 0.3%:0.1% was the formula that provided the best characteristics of chitosan carbamazepine nanoparticles.